TANTANGAN GURU DI SDN 189 PEKANBARU DALAM MENERAPKAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Lisa Jamiatu Safitri; Tria Putri Salsabilla, Suci Amelia Rambe, M. Jaya Adiputra, Mauliatun Nisa (CV. ADIBA AISHA AMIRA, 2024)
This research aims to explore the challenges faced by teachers in implementing the Strengthening Pancasila Student Profile Project (P5) at SDN 189 Pekanbaru. A qualitative approach was used in this study, with data collected through interviews with teachers teaching in grades 1, 3, and 5. The results revealed that although the teachers understood the P5 concept, there were various obstacles encountered. The main challenges included difficulties in managing young students, limited resources, and an incomplete understanding of the concept. Generally, students responded enthusiastically to P5, particularly due to project activities that connected learning to everyday life. To enhance the effectiveness of P5 implementation in the future, more intensive training for teachers, improved facilities and resources, and closer collaboration between teachers and parents are necessary